Codend Mesh Selectivity of Uroteuthis (Photololigo) duvauceli (d’Orbigny, 1848) - Madhu, V R; Meenakumari, B; Panda, Satyen Kumar (Fishery Technology, 2025)
The Indian squid, Uroteuthis (Photololigo) duvauceli (d’Orbigny, 1848) is an important resource exploited by trawlers along the northwest coast of India. The size selectivity for this species in two trawl systems viz., semi-pelagic and bottom trawls and in four mesh sizes (40, 50, 60 and 70 mm) was estimated using covered codend method. The L25, L50, L75, selection range, selection factor and selection ratio for each codend were estimated. The L50 values of Uroteuthis (Photololigo) duvauceli for the 40 and 60 mm diamond mesh codend attached to the bottom trawl were 7.90 ± 0.16 and 12.02 ± 0.21 cm dorsal mantle length (DML) respectively and the selection factors worked out to be 1.98 and 2.00. The L50 values of Uroteuthis (Photololigo) duvauceli for the 50 and 70 mm diamond mesh codend attached to the semi-pelagic trawlnet was 9.38 ± 0.12 and 16.36 ± 0.19 cm DML respectively. The selection factors derived were 1.88 and 2.34 respectively for 50 and 60 mm mesh size. In codend mesh sizes of 40 and 50 mm, 65.78 and 80.39% of the individuals caught respectively were below the size at first maturity. In 60 mm mesh size, 40.07% of the individuals was below the size at first maturity while in 70 mm mesh size all the individuals caught were below the length at first maturity.